Extinction of an employment contract for domestic workers in Spain - Ayala del Pino, Cristina (2019)
The Royal Decree 1629/2011 approaches the special employment relationship of the domestic employees to the common labor normative. However, the regulation of the extinction of employment relationship has kept the the fundamental lines its precedent. The author of this paper seeks to analyze the extinction of the employment contract of household workers in disciplinary dismissal and withdrawal; examining judicial rulings, legal literature and the current state of the subject.